Analysis of risk factors and prognostic prediction in advanced colorectal cancer undergoing immunotherapy combined with targeted therapy - Yuan, Yuan; Chen, Ya-Fang; Liu, Xiao-Mei; Hu, Ying; Hao, Shuang; Dai, Xin-Yan (Frontiers in Medicine, 2025)
BackgroundThe prognostic implications of systemic inflammatory markers in mismatch repair-proficient (pMMR) advanced colorectal cancer (CRC) treated with immunotherapy combined with targeted therapy remain unclear. This study aimed to identify key clinical and inflammatory markers predictive of overall survival (OS) and progression-free survival (PFS), and to construct a nomogram for individualized outcome prediction.MethodsThis retrospective study included 216 pMMR advanced CRC patients treated with camrelizumab plus bevacizumab between January 2020 and December 2022. Baseline clinical variables and inflammatory indices, including neutrophil-to-lymphocyte ratio (NLR), cancer-inflammation prognostic index (CIPI), and systemic immune-inflammation index (SII), were analyzed. Patients were randomly assigned to a training set (n = 139) or a validation set (n = 77). Independent prognostic factors for OS and PFS were identified via multivariable Cox regression. A nomogram was constructed and internally validated using bootstrap resampling (1,000 iterations).ResultsElevated body mass index (≥25 kg/m2) was independently associated with improved OS (hazard ratio [HR] = 0.430; 95% CI: 0.185–0.980; p = 0.047), while elevated CIPI (>828.8) and carcinoembryonic antigen (>5 ng/mL) were associated with poorer OS (HR = 1.810, p = 0.045; HR = 2.440, p = 0.025, respectively). For PFS, SII ≥ 663.9 predicted worse outcomes (HR = 2.720; 95% CI: 1.200–6.200; p = 0.016). The nomograms demonstrated moderate discrimination with optimism-adjusted C-indices of 0.610 (PFS) and 0.650 (OS), and calibration curves showed good agreement. Kaplan–Meier analysis confirmed significantly poorer OS and PFS in high-risk groups defined by nomogram scores (p < 0.001 for both).ConclusionThis study highlights the prognostic significance of both clinical and inflammatory markers in pMMR advanced colorectal cancer undergoing immunotherapy combined with targeted therapy. The developed nomogram facilitates individualized survival prediction, offering clinicians a practical tool to tailor treatment and follow-up strategies for improved patient management.